2012
DOI: 10.1177/1097184x12458590
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Cool to Care about Sexual Violence”

Abstract: We explore the paths related to college men's involvement in all-male antirape prevention groups using in-depth interviews conducted with twenty-five male college students who are active members of such groups from eleven campuses located on the East Coast of the United States. Major themes deriving from analysis of the interviews were all related to the engagement of the participants with the programs on four different levels. These themes, which are developmentally related, are (1) a disclosure which makes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…However, many authors theorize that attitude change is correlated to behavioral intentions and therefore can create shifts in behavior (Hayes, Abbott, & Cook, 2016). Piccigallo, Lilley, and Miller (2012) found that male participants in their study could identify specific changes that resulted from attending an intervention. These changes included combating sexist behavior and language of their peers and providing more support to victims of sexual assault.…”
Section: Attitude Changementioning
confidence: 99%
See 4 more Smart Citations
“…However, many authors theorize that attitude change is correlated to behavioral intentions and therefore can create shifts in behavior (Hayes, Abbott, & Cook, 2016). Piccigallo, Lilley, and Miller (2012) found that male participants in their study could identify specific changes that resulted from attending an intervention. These changes included combating sexist behavior and language of their peers and providing more support to victims of sexual assault.…”
Section: Attitude Changementioning
confidence: 99%
“…Paul and Gray (2011) found that inducing survivor empathy using female victim's stories was less effective with men. However, when male participants of these programs were given an account of sexual victimization from a male victim's perspective, they showed greater increases in attitude change and a decreased probability of future potential to perpetrate (Piccigallo, Lilley, & Miller, 2012;Schewe & O'Donohue, 1993). Berkowitz et al, (1994) suggested that programs could enhance empathy by including both male and female perspectives of victimization.…”
Section: Empathy Inductionmentioning
confidence: 99%
See 3 more Smart Citations